KEPADATAN MAKROZOOBENTOS DI PERAIRAN PEUNAGA RAYEUK, KECAMATAN MEUREUBO, KABUPATEN ACEH BARAT - Sarah, Yuni; Najmi, Nurul; Darmarini, Ananingtyas S; Heriansyah, Heriansyah (Universitas Teuku Umar, 2023)
Macrozoobenthos are aquatic organisms that live on the bottom and surface of the waters, and are influenced by bottom substrate and water quality. This study aimed at determining the density of macrozoobenthos in Peunaga Rayeuk Waters, Meureubo District, West Aceh Regency in terms of species composition, diversity, uniformity, and dominance. This research was conducted from May to June 2021 in the waters of Peunaga Rayeuk, Meureubo District, West Aceh Regency. Purposive random sampling was employed to collect the data in four stations. Based on the results of the study, 15 types of macrozoobenthos grouped into 3 classes were found, namely bivalves, gastropods and malokostraca. The macrozoobenthos density values at four stations ranged from 308.52 to 1357.49 ind/m2. The percentage value of macrozoobenthos composition by class showed that bivalves had the lowest percentage, as much as 13%, and the highest percentage was the gastropods, as much as 54%. The diversity index (H) ranged from 1.21 to 3.31 which was classified as medium to high category. The uniformity index (e) ranged from 0.81 to 0.92 and was classified as high category, while the Dominance Index (C) ranged from 0.21 to 0.54 and categorized as low to moderate category. The water quality parameter values was still in normal conditions and support the life of macrozoobenthos